Literature review on generational inheritance model and applications for Chinese family businesses - Li, Shuqi (Frontiers in Psychology, 2022)
At present, Chinese family businesses have ushered in the peak period of generational inheritance, so the issue of family business inheritance has become more and more important. The generational inheritance of family businesses is not something that can be accomplished in a short period of time, but requires a long process. There are many influencing factors, and how to choose an effective inheritance model for family businesses has always been the focus of academic circles and practitioners. At present, there is no unified conclusion about the choice of family business generational inheritance model and the factors that affect the model choice. By sorting out a large number of domestic and foreign literatures, this paper summarizes the predecessors' perspectives on the inheritance model, discusses various driving factors that may affect the current inheritance model. By further analyzes the current influencing factors on the inheritance model, this paper discusses that inheritance intention of successor may be a research perspective that has not been valued, thus proposing an expandable direction in the field of family business inheritance research.